2021
DOI: 10.1021/acs.analchem.1c00579
|View full text |Cite
|
Sign up to set email alerts
|

Improved Micro-X-ray Fluorescence Confocal Imaging of Two-Dimensional Distribution of Arsenic Concentration in Cucumber Hypocotyls Using Synchrotron Radiation

Abstract: An optimized micro-X-ray fluorescence confocal imaging (μXRF-CI) analytical method has been developed to determine the 2D distribution of elemental composition in small (1–3 mm) biological objects at a 10–20 μm spatial resolution. Plants take up chemical elements from soil, and the vascular system transports them toward shoots. In order to obtain biochemical information related to this biological process, 2D distributions of chemical elements in roots and in hypocotyls of cucumber plants were analyzed by synch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The excitation mode is exceptionally well-suited for examining biological samples within the micrometer to the millimeter size range. 50 Therefore, synchrotron-based XRF was employed to precisely determine the spatial distribution of Fe at the seed coat–embryo interface. A comparison of the seed primers with water, Fe solution, and micro-PPO-Fe (at the concentration of Fe 100 mg L –1 ) is shown in Figure 6 .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The excitation mode is exceptionally well-suited for examining biological samples within the micrometer to the millimeter size range. 50 Therefore, synchrotron-based XRF was employed to precisely determine the spatial distribution of Fe at the seed coat–embryo interface. A comparison of the seed primers with water, Fe solution, and micro-PPO-Fe (at the concentration of Fe 100 mg L –1 ) is shown in Figure 6 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…In this scenario, synchrotron radiation stands out as one of the foremost sources renowned for its ability to attain the best geometric resolution and detection limits. The excitation mode is exceptionally well-suited for examining biological samples within the micrometer to the millimeter size range . Therefore, synchrotron-based XRF was employed to precisely determine the spatial distribution of Fe at the seed coat–embryo interface.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Szaloki et al 26 presented an optimised confocal μXRF analytical approach for determining the 2D distribution of elements in small (1–3 mm) biological objects at a 10–20 μm spatial resolution. A novel quantitative algebraic reconstruction model for confocal μXRF spectrometry datasets was based on an FPM algorithm optimised specifically for the monochromatic SR beam analysis of weakly absorbing biological samples.…”
Section: Chemical Imaging Using X-ray Techniquesmentioning
confidence: 99%
“…Toxic elements, especially As and its compounds, may strongly influence the metabolic processes of plants [46]. However, we have shown that by combining XRF, FP and PCA, it is possible to perform quantitative estimation of the elements with a correlation between As content and nutrient concentrations.…”
Section: Pca Models Of µXrf and Icp-oes Analysismentioning
confidence: 99%